REINTEGRASI KONSEP MAQASHID SYARIAH DALAM ADAT BASANDI SYARA’, SYARA’ BASANDI KITABULLAH - Wimra, Zelfeni (Journal of Islamic Law Studies, 2021)
This article discusses the concept of reintegration in the implementation maqashid sharia of the cus- tomary law: Adat Basandi Syara’, Syara’ basandi Kitabullah (ABSSBK) in Minangkabau cultural region. This paper provides a scientific answer, how it should be, in practice, maqashid sharia as an integral part in ABSSBK. Methods of collecting, to analyze, and to interpretation data using compar- ative literature. The basic values compared with the concept of maqashid sharia ABSSBK. The result was found, that the terms of syara’ contained in philosophy ABSSBK have the same characteristics with maqashid sharia, but the device has not formulated detailed practical. The implications and significance, so clearly linked the value (axiology) syara’ by maqashid sharia, so it can become the reference in making ABSSBK as a basis to think, move, and arbitrate nation-state.